A Continuing narrative on Philippine theater the story of PETA (Philippine Educational Theater Association) - Samson, Laura L.; Velasco, Jovenal D. (Philippine Educational Theater Association, 2008)
"The Story of PETA may be considered a collective biography that provides a comprehensive yet intimate account of its lifework, from 1967- to 2007. It highlights the company?s unique approach and contribution to Philippine theater aesthetics, performance and pedagogy, and to popular education."--Back cover.